Pemanfaatan Serbuk Tempe Non-Lemak sebagai Pangan Fungsional melalui Pemberdayaan Kader PKK Desa Baturan - Danang Raharjo; Vivin Marwiyati Rohmana; Kharisma Jayak Pratama (Lembaga Pengembangan Kinerja Dosen, 2026)
Regarding the Utilization of Non-Fat Tempeh Powder as a Functional Food Based on Local Potential. The activity was conducted in Baturan Village, Colomadu District, Karanganyar Regency, involving 55 members of the PKK (Family Welfare Empowerment) cadre. The community service method employed a Community-Based Research (CBR) approach combined with Asset-Based Community Development (ABCD). The activities included participatory counseling, group discussions, and evaluation through pre-tests and post-tests. The results demonstrated an increase in knowledge, a shift in attitudes, and a growing awareness among the PKK cadre regarding the importance of functional food based on non-fat tempeh. Furthermore, the cadre emerged as peer educators with the potential to drive program sustainability at the community level. This community service proves that community-based counseling is effective in fostering initial social transformation towards healthier and more self-reliant food consumption patterns.